Adherence to American Society of Health-System Pharmacists Surgical Antibiotic Prophylaxis Guideline in Medical City Teaching Hospitals/Baghdad - Nagham T. Salih; Dheyaa J. Kadhim (College of Pharmacy University of Baghdad, 2017)
Surgical site infections are the second most common type of adverse events occurring in hospitalized patients. Surgical antibiotic prophylaxis refers to the use of preoperative and postoperative antibiotics to decrease the incidence of postoperative wound infections. The objective of this study was to evaluate the antibiotic administration pattern for surgical antibiotic prophylaxis and the adherence to American Society of Health-System Pharmacists surgical antibiotic prophylaxis guideline in Medical City Teaching Hospitals/Baghdad. The medical records of one hundred patients who underwent elective surgical procedures were reviewed. Adherence to the recommendations of American society of healthâ€'system pharmacists guideline was assessed for every aspect of antibiotic prophylaxis. The results of this study showed that antibiotic(s) had been administered to all of the patients involved in the study despite the fact that 34 patients (34%) were not required such prophylaxis.  While in case of administration time, 13 patients (13%) had received the antibiotic(s) at correct time while 87 patients (87%) at incorrect time. Proper antibiotic(s) selection was found in 11 patients (11.0%) only. All of the patients (100.0%) had received more than 2 doses, and all of them were not in concordance with surgical site infection prevention guidelines. In addition, 19 patients (19.0%) with surgical site infections were identified during hospital stay or within 30 days after surgery. According to these results, we can conclude that there was a substantial gap between surgical antibiotic prophylaxis guideline and their implementation in daily practice in Medical City Teaching Hospitals/Baghdad. Keywords: Surgical Antibiotic Prophylaxis Guidelines, American Society of Health System Pharmacists guidelines, Medical City Teaching Hospitals/Baghdad.